Relationships Between Remote Working and Women’s Work-Life Balance: The Example of Thrace Region (Third Sector Social Economic Review, 2025)
When the remote working is evaluated within the framework of gender stereotypes, it creates a dual structure due to women’s identification with both domestic care work and their presence in working life. This structure causes some effects on women’s work-life balance. Subject and purpose of the study is to examine the effect and relationship created by remote working on women’s work-life balance due to gender roles. Sample of the study consists of 310 remote working women in a telecommunications company in the Thrace region. Participants perceptions of remote working do not differ according to “age group, educational status, marital status and having children”. While the participants work life balance does not differ according to “educational status, length of service in remote working and location where they work remotely”; the participants work life balance differs according to “age group, marital status, having children and satisfaction level of remote working”. In addition, there is a significant relationship between the dimensions of remote working and the dimensions of work life balance. Finally, remote working positively affects the dimension of work life balance “work life harmony” and negatively affects the dimensions of “neglecting life, taking time for oneself and life consisting of only work”.
Keywords: Remote work; Work life balance; gender; woman; telecommunications